Edukasi tentang Kanker Serviks pada Ibu PKK di Desa Sudimara Kecamatan Cilongok - Hanan Isra Pratama; Atun Raudotul Ma’rifah; Noor Yunida Triana (Journal of Community Service and Engagement, 2026)
This community-based service program aimed to analyze the effectiveness of cervical cancer education in improving the knowledge of PKK women in Sudimara Village, Cilongok District. The program applied an empirical approach using a one group pre-test post-test design involving 20 participants selected through total sampling. Educational interventions were delivered through lectures, participatory discussions, demonstrations, PowerPoint presentations, leaflets, and audiovisual media focusing on cervical cancer risk factors, symptoms, prevention, and early detection strategies. Data were collected using structured questionnaires administered before and after the intervention and analyzed descriptively to identify changes in participants’ knowledge levels. The findings demonstrated a substantial improvement in participants’ understanding of cervical cancer prevention and early screening practices after the educational intervention. Active participant involvement during discussions also indicated the emergence of community-based knowledge transfer and strengthened awareness regarding preventive reproductive health behavior. The program contributed not only to cognitive improvement but also to the reinforcement of community capacity in promoting early detection and cervical cancer prevention at the village level.